2021
DOI: 10.1097/phm.0000000000001870
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis Investigating the Pain-Relieving Effect of Interferential Current on Musculoskeletal Pain

Abstract: Background: Interferential current is one of the most common electrotherapeutic modalities used in the treatment of painful conditions. Patients seeking medical help to reduce their musculoskeletal pain can be treated using interferential current. Objective: The current review aimed to analyze the recently available information regarding the efficacy of interferential current in alleviating the pain of musculoskeletal origin. Methods: This study used Scopus, CINAHL, Cochrane Library, Web of Science, MEDLINE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
(296 reference statements)
1
10
0
Order By: Relevance
“…They concluded that IFC therapy alone reduced pain compared to placebo. Nevertheless, there were no significant differences between IFC and other interventions, such as laser, TENS or cryotherapy; IFC therapy plus standard treatment and placebo IFC therapy plus standard treatment; or IFC therapy plus standard treatment and standard treatment [33].…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…They concluded that IFC therapy alone reduced pain compared to placebo. Nevertheless, there were no significant differences between IFC and other interventions, such as laser, TENS or cryotherapy; IFC therapy plus standard treatment and placebo IFC therapy plus standard treatment; or IFC therapy plus standard treatment and standard treatment [33].…”
mentioning
confidence: 76%
“…We found 4 systematic reviews that investigated the efficacy of IFC for musculoskeletal pain [32,33] and knee osteoarthritis [9,34].…”
Section: Scientific Evidence Of Ifc 71 Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapy, one of the initial treatment options for DJD, includes various measures. The treatment modalities such as the use of low-level ultrasound, interference currents, low-intensity lasers, and ultrashort waves can reduce inflammation, promote microcirculation, and relax masticatory muscles to obtain analgesic effects and improve joint mobility [ 31 33 , 42 ]. Manual therapy can improve blood circulation, reduce muscle spasms, relax muscles around joints, rearrange soft tissue, reduce joint adhesion, increase the joint’s range of motion, and reduce pain [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary advantages of IFC lies in its ability to reduce skin impedance, enabling it to penetrate deeper into the tissues. IFC not only enhances circulation and alleviates pain by stimulating large nerve fibers but also restores the neurovegetative balance, thereby modulating the sympathetic nervous system and promoting muscle relaxation, potentially contributing to pain alleviation [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%